PENGARUH MODEL PEMBELAJARAN TEBAK KATA TERHADAP HASIL BELAJAR PPKn SISWA KELAS VII SMP NEGERI 1 KUNTO DARUSSALAM - Rahmayanti Gusnita; Gimin '; Sri Erlinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the lack of ppkn student learning outcomes in SMP Negeri 1 Kunto Darussalam. Formulation of the problem in this research is : “how the influence of the learning model charades on learning outcomes of students of class VII PPKn SMP Negeri 1 Kunto Darussalam?”. This reaserch aimed to determine the effect of charades learning model to the learning outcomes of students in learning PPKn in SMP Negeri 1 Kunto Darussalam in july 2016. This research is a qualitative descriptive study, the population in this research were students of class VII SMP Negeri 1 Kunto Darussalam. Sempel in the research is class VII 2 (control class) students were given a lecture and class VII 1 (experimental class) students by learning model charades then the data were analyzed using normality test, homogeneity test and test “t”. Based on the results of the research show that there are positive influence on learning outcomes of students who applied learning models charades compared to using conventional methods in SMP Negeri 1 Kunto Darussalam with the price (, 3,74 ≥ 1,9977). Thus obtained the hypothesis there is a significant positive effect of the application of the model of charades with student learning outcomes VII 1 SMP N 1 Kunto Darussalam acceptable.Key Words:Learning Outcomes, Models Charades